AKUNTANSI PERPAJAKAN DALAM PENGGABUNGAN USAHA (Studi Kasus Pada Perusahaan Listed Di BEI) - Hendrian, Hendrian; Muktiyanto, Ali (Jurnal Organisasi Dan Manajemen, 2011)
In accounting, there are two methods used in recording business combinations i.e purchase and pooling of interest method. Purchase method has ameasurable indication with the withdrawal of cash beside the cost of business combination and stock issuance costs incurred by the company buyer. In addition to that, there will be changes of ownership. The assets acquired by a business entity are recorded and recognized at market value. As a consequence, the excess of fixed assets will be recorded as goodwill. Meanwhile if the business combination uses the pooling of interest method, then the amount of assets, debts and rights of shareholders that are reported by the affiliated companies will be recognized in accordance with its book value. APB No.16 notes that there are 12 requirements that must be met when using pooling of interest method. If it does not meet any of these requirements then the combined companies must use the purchase method. There is no goodwill in pooling interest method. It means that in the merger process there is no obligation to pay taxes since it based on book value and no goodwill.